Analisis Pengukuran Produktivitas Perusahaan Alsintan CV. Cherry Sarana Agro - Prima Fithri; Regina Yulinda Sari (Jurnal Optimasi Sistem Industri, 2015)
CV Cherry Sarana Agro is a manufacturing company, which produces agricultural machinery. In reality, company evaluatesits work and performance based on level of profits. In order to maintain the company's performance, it is necessary to measures the productivity of company to see how effective the performance of this company. So it can be determined what is needed in order to improve the performance of the company and also can increase profits. Measuring the productivity can be seen from the financial data that obtained from the company. Then based on data processing, show this company's productivity levels decreased during the period of measurement and it means company requires efforts to increase the efficient use of inputs. It is necessary for company to increase its productivity for the future. This improvement was made by taking into account the partial productivity as inputs that affect the profitability of the company on an ongoing basis.